Running sprint force-velocity-power profile obtained with a low-cost and low frame rate acquisition video technique: reliability and concurrent validity - Barros Sousa, F. A.; Marinho, A. H.; da Silva Calvalcante, M. D. S.; de Almeida Rodrigues, N. A.; Lima, T. S.; da Silva, D. G.; de Souza Fonseca, F.; Balikian Junior, P.; de Araujo, G. G. (Sports Biomechanics, 2025)
The Force-velocity (F-v) and Power-velocity (P-v) relationships quantify athlete`s horizontal force production capacities during sprinting. Efforts are underway to enhance ecological validity for practitioners and sports coaches. This study provides detailed data comparison of a low frames per second setup (30 Hz; FPSlow) with splits from a high FPS camera to derive F-v and P-v relationships. Sixty-six sprints performed by 11 university track and field athletes (6 male, 5 female) were evaluated. Data were recorded using FPSlow, photocells, and a high-speed camera (240 Hz; MySprint). In the FPSlow setup, bias was 0.17s, and Limits of agreement was 0.09s compared to photocells. ICC was 1.00, and the coefficient of variation (CV) was 1.0% [0.8-1.1%]. Time acquisition comparison between MySprint and FPSlow setups revealed high consistency (ICC = 0.99) and low CV (2.9% [2.8-3.1%]). F-v profile variables exhibited biases from trivial to small, with ICC ranging from moderate to nearly perfect. CV ranged from 2.7% to 11.8%, and improved using the average of three sprints (CV between 1.8% and 8.6%). The `simple method` applied to data from the low FPS video setup yielded kinetic and kinematic parameters comparable to those obtained by the validated previous method and photocells.